NGO's as stakeholders in corporate social investment in South Africa - Diedricks, Razia (My University, 2014)
The research project examines the context in which modern-day CSI practises have unfolded in South Africa. It examines the space occupied by NGOs in the practise against the backdrop of post-apartheid policies and legal frameworks. The report presents the findings that due to the high level of developmental challenges in South Africa accompanied by the country’s unique legacy of apartheid, the practice has unfolded along racial prescriptions, particularly in the form of Broad Based Black Economic Empowerment (BBBEE). Various requirements in the form of donor prescriptions and interventions as well as compliance with policy has led to the practise being formalised leading to structural changes in many NGOs which has been accompanied by both positive and negative implications. The findings challenge the notion that NGOs are dancing to the donors tune based on their resource dependence and posits that a more emphatic articulation of the currency and value which NGOs possess in the form of values, knowledge, creativity, experience and expertise could result in more strategic engagement with donors that could lead to sustainable partnerships versus the current state of philanthropy based CSR.